Readability measurement of the 7th grade Farsi textbook (academic year 1395-96) based on Fog, Fry and Flesch formula - Zohreh Sedighifar; Shohreh Sādāt Sajjādi; Behnām Alavi Moghadam (فصلنامه نوآوری‌های آموزشی, 2017)
This study was going to measure the readability of the 7th grade Farsi textbook (academic year 1395-96) based on the three readability formula. We wanted to find out how much the mentioned book is in accordance with the readability formula from the viewpoint of the principles of the material development. The research method was descriptive content analysis according to Fog, Fry and Flesch formula. The research questions included: 1. is the readability of the book’s material in accordance with the 7th grade students, considering their age and learning levels criteria? 2. Could the material and content of the book be learnt without the teacher, independently? 3. Have the principles of curriculum planning, including the principle of simple to difficult, been observed in the development of the textbook? 4. How much the readability of the related textbook measured by the Fog, Fry and Flesch formula correspond to each other? Findings showed that in the 7th grade Farsi textbook of the 1395-96 academic year: 1. the content is not in accordance with the 7th grade level. According to the Fog, Fry and Flesch formula, the readability of this book is at the level of the University and even it is appropriate for the higher levels. 2. Due to the very much difficulty of the material, the textbook could not be used independent of the teacher. 3. The material at the beginning, middle and end of the textbook shows that to some extent the principle of simple to difficult has been observed according to the Fog formula, but not according to the Fry and Flesch formula. 4. The readability of the mentioned textbook measured by Fog, Fry and Flesch formula correspond to each other to a great extent.